2018
DOI: 10.1177/0967828x18769393
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian presidents and communal violence against non-mainstream faiths

Abstract: Indonesia in the post-New Order era saw frequent incidents of religious violence. These began with bloody sectarian conflicts in the cities of Ambon and Poso, which pitted Muslims against Christians. During the era of President Susilo Bambang Yudhoyono (2004–2014), heresy campaigns against non-mainstream faiths (Ahmadiyah and Shi’a) increased, followed by attacks mainly levelled at properties belonging to members of these minority communities. Scholars have argued that Yudhoyono and his predecessors, Abdurrahm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The choice of Pancasila as an ideology and outlook on life is not a consensus only, but it is because Pancasila has values that reflect the personality and customs of the previous Indonesian people, meaning that the values of Pancasila are values that live and develop in people's lives since this nation existed. Philosophically, Pancasila also has universal values that are ideal, so that Pancasila values are an ideal character to be used as guidelines in everyday life [5]. In fact, in addition to being a guide in everyday life, Pancasila is also used as a guideline in the system of government and state, so that the five precepts contained in Pancasila must not be separated and constitute a unified system [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of Pancasila as an ideology and outlook on life is not a consensus only, but it is because Pancasila has values that reflect the personality and customs of the previous Indonesian people, meaning that the values of Pancasila are values that live and develop in people's lives since this nation existed. Philosophically, Pancasila also has universal values that are ideal, so that Pancasila values are an ideal character to be used as guidelines in everyday life [5]. In fact, in addition to being a guide in everyday life, Pancasila is also used as a guideline in the system of government and state, so that the five precepts contained in Pancasila must not be separated and constitute a unified system [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that jihad was used to justify violence toward the Ahmadiyya community (Burhani 2021). Other studies showed the links between the conflicts with SKB and the discrimination against minorities (Sodik et al 2022;Connley 2016), the absence of state (Qurtuby 2012;Suryana 2018), the discourse of media in covering religious conflicts (Dulwahab et al 2021), the peace process (Almujaddidy 2017;Noor 2015;Fadhillah 2017), and the fulfillment of the Ahmadiyya adherents' civil rights (Wahab 2015). Under the administration of President Yudhoyono, there were many civil rights violations against Ahmadiyya adherents, including withholding the issuance of identity cards (Kartu Tanda Penduduk/KTP) (Pamungkas 2018) and Family Cards (Kartu Keluarga/KK) (Almujaddidy 2017), marriage registration, and birth certificates (Hicks 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After the fall of Suharto in 1998, the heresy campaign against the Ahmadiyya has become more intense and has sometimes involved physical attacks. Scholars have commonly focused on the issues of human rights, citizenship, political and social authority, media propaganda or media reports, and the capability of government in managing diversity when discussing the resistance, attack, and heresy campaign against the Ahmadiyya (Connley 2016; Crouch 2011; Hicks 2014; Putra et al 2018; Soedirgo 2018; Suryana 2016, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Suryana (2016, 2018, 2019), for instance, discusses agency and structure in the rising of intolerance and violence against minority religious groups. He argues that violence against the Ahmadiyya was possible because of security officials’ entangled relations with vigilante groups, together with the inclination of some state institutions to preserve a majoritarian social order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation